Commoning in the Digital Era: Platform Cooperativism as a Counter to Cognitive Capitalism - Zygmuntowski, Jan J. (Praktyka Teoretyczna, 2018)
With the widespread adoption of ICT technologies, platforms, social media and sharing economy businesses have emerged as models of economic organization. This paper examines their functioning on a micro level to provide a thorough critique. The theory of cognitive capitalism and opposing arguments are explored in order to bring a holistic understanding and observe how value is captured and accumulated with the use of technological apparatuses. Cognitive capitalism is not uniform, however, and recognition of the special properties displayed by networks makes it possible to identify the challenge posed by the rising array of netarchist platforms. Platform cooperativism is the proposed egalitarian and long-term sustainable counter, as it aims to design new tools in line with the commons paradigm. Finally, the paper provides key insights into the specifications, difficulties, and next steps required to lead to better platform co-ops and a better future.